REMEDIAL AND CORRECTIVE FEEDBACK STRATEGIES FOR IMPROVING STUDENTS’ ENGLISH LANGUAGE PROFICIENCY - Maawa, Paul Kharlo L.; Ortega-Dela Cruz, Ruth (Universitas Negeri Makassar, 2019)
The study used descriptive research design to evaluate the use of remedial and corrective feedback strategies in improving students’ English language proficiency. Purposive sampling of English teachers and secondary students were surveyed and interviewed to address the research objectives. Descriptive statistics were used to analyse the data gathered using researcher-made instrument. Findings show that peer support program and handling students’ behaviour problems were the most commonly used remedial strategies by the English teachers whereas, explicit correction, clarification request, recast, elicitation and paralinguistic signal were the commonly used corrective feedback strategies in teaching English. Cross-examination in the students’ grades indicates positive effect of remedial and corrective feedback strategies in improving the English language proficiency of the students. The teachers know well how to use corrective feedback strategies although some might not be aware that they are using it. Corrective feedback should also come first since it can be incorporated in the remedial teaching strategy while the teacher is conducting remedial classes. This will further enhance their teaching while providing concrete ways to help improve the students’ English language proficiency.